Drug Distribution and Penetration of Foam-Based Intraperitoneal Chemotherapy (FBIC) - Carolina Khosrawipour; Jakub Nicpoń; Zdzisław Kiełbowicz; Przemysław Prządka; Bartłomiej Liszka; Veria Khosrawipour; Said Al-Jundi; Shiri Li; Hien Lau; Joanna Kulas; Piotr Kuropka; Agata Diakun; et al. (MDPI AG, 2023)
For decades, intraperitoneal chemotherapy (IPC) was used as a liquid solution for the treatment of peritoneal metastasis. Due to its advantageous physical properties, foam-based intraperitoneal chemotherapy (FBIC) was recently proposed as a treatment for peritoneal metastasis. For the first time, this study intends to examine the feasibility, expansion, drug distribution, and penetration of FBIC in vivo. Three swine received contrast-enhanced FBIC doxorubicin delivered using a bicarbonate carrier system. During the procedure, intraoperative blood analyses and periumbilical diameter, as well as foam distribution, penetration, and expansion of the FBIC were analyzed. The swine received an abdominal CT scan to evaluate the contrast distribution. Furthermore, a hematoxylin-eosin (HE) staining of peritoneal samples was performed, and fluorescence microscopy was conducted. FBIC was performed without complications. The periumbilical diameter peaked after 5 min and then decreased. Blood analyses showed changes in blood parameters, with a reduction in the pH levels of serum calcium and potassium. CT scan detected contrast-enhanced FBIC throughout the abdominal cavity. Fluorescence microscopy confirmed that all areas were exposed to doxorubicin and no pathologies were detected in the HE histology. Our preliminary results are quite encouraging and indicate that FBIC is a feasible approach. However, in order to discuss possible clinical applications, further studies are required to investigate the pharmacologic, pharmacodynamic, and physical properties of FBIC.